1996
DOI: 10.1111/j.1432-1033.1996.0601r.x
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding Kinetics of Bovine Trypsinogen

Abstract: The unfolding kinetics of bovine trypsinogen were studied by a fluorescence-detected stopped-flow technique at pH 5.8. Trypsinogen unfolding appeared to be a rather complex reaction. Two phases, fast (with a time constant in the millisecond range) and slow, were detected in the range 2-7 M guanidium chloride (GdmCI). The natural logarithm of the rate constant of the slow phase exhibited strong dependence on [GdmCl], changing from hundreds of seconds at low denaturant concentration to about 20 ms at 7 M GdmC1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The fast phase is not a single-phase event under mildly denaturing conditions and in the slow phase the authors showed evidence of intermediates accumulating under strongly folding conditions. A similar kinetics was observed for the trypsinogen-Ca 2+ complex and limited data on trypsin unfolding show a virtually identical behavior (13). More recently Ruan et al (14) studied the effect of hydrostatic pressure on the unfolding of bovine trypsin.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The fast phase is not a single-phase event under mildly denaturing conditions and in the slow phase the authors showed evidence of intermediates accumulating under strongly folding conditions. A similar kinetics was observed for the trypsinogen-Ca 2+ complex and limited data on trypsin unfolding show a virtually identical behavior (13). More recently Ruan et al (14) studied the effect of hydrostatic pressure on the unfolding of bovine trypsin.…”
Section: Introductionsupporting
confidence: 60%
“…The authors showed that the stability of trypsinogen is increased by calcium ion, by the dipeptide Ile-Val and by basic pancreatic trypsin inhibitor (BPTI) and proposed a two-state transition in equilibrium. The unfolding kinetics of trypsinogen was studied by Otlewski et al (13) using a fluorescencedetected stopped-flow manifesting two independent phases. The fast phase is not a single-phase event under mildly denaturing conditions and in the slow phase the authors showed evidence of intermediates accumulating under strongly folding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no research has been carried out to investigate the eŠects of bioactive molecules present in the extract of this medicinal plant on human neutrophil elastase (HNE) activity. This enzyme has been reported to play a crucial role in extracellular proteolytic processes at sites of in‰ammation [11][12][13] and capable of cleaving many proteins with important biologic functions, especially elastin, an important extracellular matrix protein that plays a mechanical function in the lungs. Thus it became evident that HNE is involved in the pathogenesis of diŠerent in‰ammatory diseases such as emphysema, cysticˆbro-sis (CF), and COPD.…”
Section: Introductionmentioning
confidence: 99%
“…The question of whether these proteins need the tails for correct refolding, as does PCI, is an interesting issue. The trypsin squash inhibitors have a very similar structural topology to PCI and the same disulfide bridge pattern (28). The sequence alignment of a large number of the squash inhibitors shows that the cysteine-reinforced core contains 25 amino acids (27 in PCI); there are zero to five amino acids at the N terminus and, in most cases, only one glycine residue at the C terminus, after the last cysteine of the T-knot core.…”
Section: Discussionmentioning
confidence: 97%
“…If the fourth residue of the C terminus, Pro 36 , is also deleted, no formation of the native-like species is detected. Both in the NMR and x-ray structure of PCI, a hydrogen bond between the carbonyl oxygen of Pro 36 (in the tail) and the amide nitrogen of Trp 28 (in the core) is observed. Our results seem to indicate that this hydrogen bond, which could be formed by any residue in position 36, could participate significantly in directing the native disulfide pairing of PCI.…”
Section: Discussionmentioning
confidence: 98%